Investigation of Mechanical Properties for Open Cellular Structure CoCrMo Alloy Fabricated by Selective Laser Melting Process - A., Azidin; Z. A. M., Taib; W. S., Wan Harun; S. A., Che Ghani; M. F. F., Ab Rashid; M. A., Omar; H., Ramli (IOP Publishing, 2015)
Orthodontic implants have been a major focus through mechanical and biological performance in advance to fabricate shape of complex anatomical. Designing the part with a complex mechanism is one of the challenging process and addition to achieve the balance and desired mechanical performance brought to the right manufacture technique to fabricate. Metal additive manufacturing (MAM) is brought forward to the newest fabrication technology in this field. In this study, selective laser melting (SLM) process was utilized on a medical grade cobalt-chrome molybdenum (CoCrMo) alloy. The work has focused on mechanical properties of the CoCrMo open cellular structures samples with 60 %, 70 %, and 80 % designed volume porosity that could potentially emulate the properties of human bone. It was observed that hardness values decreased as the soaking time increases except for bottom face. For compression test, 60 % designed volume porosity demonstrated highest ultimate compressive strength compared to 70 % and 80 %.